Effect of anticoagulation on the incidence of venous thromboembolism, major bleeding, and mortality among hospitalized COVID-19 patients: an updated meta-analysis - Chen, Xinwang; Zhang, Suyun; Liu, Haiyu; Zhang, Qianyuan; Chen, Jinghan; Zheng, Qixian; Guo, Ningjing; Cai, Yuanyuan; Luo, Qiong; Xu, Qian; Yang, Sheng; Chen, Xiangqi (Frontiers in Cardiovascular Medicine, 2024)
Objective: Anticoagulation is crucial for patients hospitalized with coronavirus disease 2019 (COVID-19) due to the high risk of venous thromboembolism (VTE). However, the optimal anticoagulation regimen needs further exploration. Therefore, we evaluated the efficacy and safety of diverse anticoagulation dosage dosages for COVID-19.Methods: An updated meta-analysis was performed to assess the effect of thromboprophylaxis (standard, intermediate, and therapeutic dose) on the incidence of VTE, mortality and major bleeding among COVID-19 patients. Literature was searched via PubMed, EMBASE, Web of Science, and China National Knowledge Infrastructure (CNKI) database. The odds ratio (OR) and 95% confidence interval (CI) were calculated for effect estimates.Results: Nineteen studies involving 25,289 participants without VTE history were included. The mean age of patients was 59.3 years old. About 50.96% were admitted to the intensive care unit. In the pooled analysis, both therapeutic-dose and intermediate-dose anticoagulation did not have a significant advantage in reducing VTE risk over standard dosage (OR=1.09, 95% CI: 0.58-2.02, and OR=0.89, 95% CI: 0.70-1.12, respectively). Similarly, all-cause mortality was not further decreased in either therapeutic-dose group (OR=1.12, 95% CI: 0.75-1.67) or intermediate-dose group (OR=1.34, 95% CI: 0.83-2.17). While the major bleeding risk was significantly elevated in the therapeutic-dose group (OR=2.59, 95%CI: 1.87-3.57) as compared with the standard-dose regimen. Compared with intermediate dosage, therapeutic anticoagulation did not reduce consequent VTE risk (OR=0.85, 95% CI: 0.52-1.38) and all-cause mortality (OR=0.84, 95% CI: 0.60-1.17), but significantly increased major bleeding rate (OR=2.42, 95% CI: 1.58-3.70). In subgroup analysis of patients older than 65 years, therapeutic anticoagulation significantly lowered the incidence of VTE in comparation comparison with standard thromboprophylaxis, however, at the cost of elevated risk of major bleeding.Our results indicated that for most hospitalized patients with COVID-19, standard-dose prophylactic anticoagulation might be the optimal choice. For elderly patients at low risk of bleeding, therapeutic-dose anticoagulation could further reduce VTE risk and should be considered especially when there were other strong risk factors of VTE during hospital stay.